Respuesta :
Answer:
A. When x = 3, both expressions have a value of 30.
Step-by-step explanation:
The first expression is 4(x+3)+2x
The second expression is 6(x+2).
When we substitute x=3 into the first equation, we get:
[tex]4(3 + 3) + 2(3) = 4 \times 6 + 6 = 24 + 6 = 30[/tex]
When we substitute x=3 into the second expression we get:
[tex]6(3 + 2) = 6(5) = 30[/tex]
This proves that the two expressions are equivalent.
The correct choice is A
Answer: A
Step-by-step explanation:
Hope this helps can i have brainly-est please